Three steps towards practical application of public transport route optimisation in urban areas - Heyken Soares, Philipp (2020)
The research on computer-based optimisation of public transport networks has seen huge advances in recent years. However, there is almost no application of its results in real-world planning processes. A review of the literature identifies several possible reasons for this: a) many developed algorithms do not consider important details for urban applications, b) methods to generate the required input datasets struggle when applied to irregular urban networks, or c) the absence of an interface to use the developed algorithms with transport modelling software. The three publications presented in this thesis address these three issues.